2005
DOI: 10.1002/eat.20128
|View full text |Cite
|
Sign up to set email alerts
|

Night eating syndrome in young adult women: Prevalence and correlates

Abstract: NES was rare in this sample of young women. Low comorbidity of NES with other eating disorders suggests that NES may be distinct from the DSM-IV recognized eating disorders. Longitudinal data are needed to determine the long-term health implications of this behavioral pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
4
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 31 publications
1
51
4
1
Order By: Relevance
“…Despite that, overweight has not been identified as a crucial clinical sign of NES in young adults. 19 Future assessment of weight in this population would be interesting nonetheless, as little is published about eating patterns and weight in this culture. Additionally, depressed mood and anxiety symptoms were not assessed with validated measures, so no information is available for the divergent and convergent validity of the NEQ.…”
Section: Discussionmentioning
confidence: 98%
“…Despite that, overweight has not been identified as a crucial clinical sign of NES in young adults. 19 Future assessment of weight in this population would be interesting nonetheless, as little is published about eating patterns and weight in this culture. Additionally, depressed mood and anxiety symptoms were not assessed with validated measures, so no information is available for the divergent and convergent validity of the NEQ.…”
Section: Discussionmentioning
confidence: 98%
“…16 At present, NES is not formally listed as an eating or sleep disorder, and no agreed diagnostic criteria exist. NES prevalence estimates are low in community samples (range: 0.4-1.6%), 5,17,18 but markedly higher among groups of obese persons seeking medical or surgical weight loss (range: 6-64%). 19 Despite this, only one cross-sectional study has shown a positive relationship between NES and body mass index (BMI).…”
Section: Introductionmentioning
confidence: 89%
“…However, few studies have controlled for the influence of binge eating. Those that have controlled for binge eating have reported similar levels of psychological functioning between NES and non-NES in a normal weight sample of Black females 18 and an obese sample. 8 Another study, which notably diagnosed NES by consumption of X25% total energy after the evening meal and/or awakenings to eat X3 times in a week (nocturnal snacking), did report a positive association between NES and symptoms of depression in obese NES compared to weight-matched controls.…”
mentioning
confidence: 93%
“…Prevalence studies suggest a rate of <0.5% to approximately 1.6% in general population samples of adults and children [5][6][7][8] and 6%-42% in obesity clinic and prebariatric surgery patients. 3 Wakeful nighttime eating appears to be a frequent symptom that appears to be more common in treatment-seeking obese participants than in community samples of all weights.…”
Section: Introductionmentioning
confidence: 99%